Revealing the etching process of water-soluble Au25 nanoclusters at the molecular level - Yitao Cao (Nature Portfolio, 2021)
Etching is one of the key considerations in the synthesis, storage, and application of metal nanoparticles. Here, the authors study the etching of water-soluble thiolate-protected gold nanoclusters at a molecular level and reveal an unusual recombination process in the oxidative reaction environment.